PENGARUH KECANGGIHAN MESIN TERHADAP AKURASI UKURAN KAYU GERGAJIAN - Jamal Balfas (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
This study was carried out at a sawmill in Lampung, Sumatera. The sawmill had two unit of band-headrigs with different type of machines, namely a conventional mill and a modern one. The design of the modern mill is more sophis- ticated in characteristics as figured in Table 1. Accuracy of sawn timber was determined by comparison between actual size and target size of the lumber thickness. The data were collected from measurement of 1OO pieces of lumber selected randomly from each mill production.The result showed that the machine sophistication has a significant effect on sawn timber size accuracy. The more sophisticated machine can give more than 10% benefit of sawn timber production compared to the conventional one. The level of sawing accuracy on conventional mill is 88.15%, whereas the modern mill could reach 98.29%.